PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 009 BATURIJAL HILIR KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Jesika, Domi Adrian; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the lack of teachers in the use of mastery learning model IPS. As for the teachers who often do just conventional learning so that learning becomes menoton and students do not have the ability to discuss, motivated and ultimately affect learning outcomes. Based on the problems it is necessary to find a way to solve those problems. Among them are applying the quantum model of teaching that is more attractive to the environmental conditions of students in everyday life. Quantum teaching models provide an opportunity for students to learn with a nice atmosphere. In accordance with the concept of quantum teaching that "the world bring them into our world, and deliver our world into their world" so that learning model of quantum teaching can improve learning outcomes IPS Elementary School third grade students 009 Baturijal Hilir District of Peranap. The subjects were students of class IIIB Elementary School 009 Baturijal Peranap Hilir District of academic year 2014/2015 the number of students 20 people. This research was conducted in two cycles with two meetings with two replications end. This research data collection instruments were observation sheet student, teacher observation sheet and repeat the test end of the cycle. The study is in the form of classroom action research (PTK), aims to drive the learning outcomes IPS Elementary School third grade students Baturijal 009 Downstream on the material usability money. These results indicate that the model of Quantum Teaching learning can improve student learning outcomes IPS. IPS student learning outcomes can be seen from the increase in base score with an average of 58.3 in the category of not being able, first cycle with an average of 68 to afford categories and second cycle the average value of 79 with categories capable. Evident from the average score of the base, the first cycle and second cycle increase occurred in the first cycle by 18% and experienced a very significant increase seen in the second cycle by 36%. Results obtained data refer to the standard of learning outcomes IPS capabilities, and it means that the model of Quantum Teaching learning can improve learning outcomes IPS Elementary School third grade students 009 Baturijal Hilir District of Peranap. Keywords : Quantum Learning Model Teaching , IPS